Gendered analysis of rice product profiles, Côte d’Ivoire - Ndour, Maimouna; Ly, Cheikh Oumar; Kokola Assienan, Juliette; Mujawamariya, Gaudiose; Yadav, Shailesh (Africa Rice Center, 2024)
Rice varieties are distinguished by characteristics which may differ depending on the farmers' preferences, rice cooking and consumption habits, environmental conditions, and water management's practices. These characteristics explain adoption of new varieties; hence incorporating gendered preferred varietal characteristics can support modern breeding achieve its adoption targets. The gendered traits were assessed through a qualitative approach in five rice production areas in Cote d’Ivoire, representing the product profiles for DELS_U market segment in upland ecology (Korhogo, Odienné), TELS_R, TMeLS_R in rainfed lowland ecology (Odiénné, Gagnoa) and TELS_I in irrigated lowland (Gagnoa, Daloa, Yamoussoukro).